2013
DOI: 10.1007/s10585-013-9585-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and mechanism of action of Deguelin in suppressing metastasis of 4T1 cells

Abstract: Cancer related deaths in breast cancer patients are due to metastasis of the disease. Murine 4T1 cells (Murine mammary cancer cell line developed from 6-thioguanine resistant tumor) provide an excellent research tool for metastasis related studies because these cells are highly aggressive and readily metastasize to the lungs. In this study we determined the effect of Deguelin on in vivo/vitro growth and metastasis of 4T1 cells. Deguelin inhibited the in vitro growth of 4T1 cells in a time and dose dependent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Several studies have already demonstrated its excellent potential as an anticarcinogenic and antiproliferative agent against various malignant tumors including gastric, lung and breast carcinoma, by targeting apoptosis, cell cycle arrest and anti-angiogenesis (5-7). Deguelin also exhibits effects of anti-metastasis (7,8). It inhibits cancers through a number of pathways, including the PI3K-Akt, HIF-1-VEGF, IKK-IκBα-NF-κB, EMT and AMPK-mTOR-survivin pathways (4-7).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already demonstrated its excellent potential as an anticarcinogenic and antiproliferative agent against various malignant tumors including gastric, lung and breast carcinoma, by targeting apoptosis, cell cycle arrest and anti-angiogenesis (5-7). Deguelin also exhibits effects of anti-metastasis (7,8). It inhibits cancers through a number of pathways, including the PI3K-Akt, HIF-1-VEGF, IKK-IκBα-NF-κB, EMT and AMPK-mTOR-survivin pathways (4-7).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that flavonoid compounds can protect the liver through multiple pathways, such as by preventing high liver iron levels, inhibiting lipid peroxidation and hepatic protein oxidation, and facilitating iron excretion (Feher and Lengyel, 2012;Sak, 2014). Additionally, flavonoid compounds have a stronger anti-oxidative activity than vitamin C and vitamin E (Mehta et al, 2013). In contrast, flavonoid compounds can exert their protective role by regulating cell apoptosis; these compounds can inhibit normal hepatic cell apoptosis while accelerating apoptosis of tumor cells and necrotic hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…4T1 cells (American Type Culture Collection—ATCC), a widely used triple negative breast cancer cell line [18,19] and a murine model for stage IV human breast cancer, were grown at 37°C with 5% CO 2 in RPMI-1640 supplemented with 10% fetal bovine serum (FBS), 100 units/mL penicillin and 50 g/mL streptomycin, all from GIBCO (Grand Island, NY). MDA-MB-231 and MDA-MB-468, also triple negative breast cancer cell lines, however, derived from human breast tumors, were purchased from ATCC and cultivated at 37°C with 5% CO 2 in DMEM medium supplemented with 10% FBS, 100 units/mL penicillin and 50 g/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%